Genome-Wide Identification, Cloning and Functional Analysis of the Zinc/Iron-Regulated Transporter-Like Protein (ZIP) Gene Family in Trifoliate Orange (Poncirus trifoliata L. Raf.) - Fu, Xing-Zheng; Zhou, Xue; Xing, Fei; Ling, Li-Li; Chun, Chang-Pin; Cao, Li; Aarts, Mark G. M.; Peng, Liang-Zhi (Frontiers in Plant Science, 2017)
Zinc (Zn) and iron (Fe) deficiency are widespread among citrus plants, but the molecular mechanisms regarding uptake and transport of these two essential metal ions in citrus are still unclear. In the present study, 12 members of the Zn/Fe-regulated transporter (ZRT/IRT)-related protein (ZIP) gene family were identified and isolated from a widely used citrus rootstock, trifoliate orange (Poncirus trifoliata L. Raf.), and the genes were correspondingly named as PtZIPs according to the sequence and functional similarity to Arabidopsis thaliana ZIPs. The 12 PtZIP genes were predicted to encode proteins of 334–419 amino acids, harboring 6–9 putative transmembrane (TM) domains. All of the PtZIP proteins contained the highly conserved ZIP signature sequences in TM-IV, and nine of them showed a variable region rich in histidine residues between TM-III and TM-IV. Phylogenetic analysis subdivided the PtZIPs into four groups, similar as found for the ZIP family of Arabidopsis thaliana, with clustered PtZIPs sharing a similar gene structure. Expression analysis showed that the PtZIP genes were very differently induced in roots and leaves under conditions of Zn, Fe and Mn deficiency. Yeast complementation tests indicated that PtIRT1, PtZIP1, PtZIP2, PtZIP3, and PtZIP12 were able to complement the zrt1zrt2 mutant, which was deficient in Zn uptake; PtIRT1 and PtZIP7 were able to complement the fet3fet4 mutant, which was deficient in Fe uptake, and PtIRT1 was able to complement the smf1 mutant, which was deficient in Mn uptake, suggesting their respective functions in Zn, Fe, and Mn transport. The present study broadens our understanding of metal ion uptake and transport and functional divergence of the various PtZIP genes in citrus plants.